Optical and Structural Properties of Nitride Based Nanostructures - Bertram, Frank; Berger, Christoph; Christen, Jürgen; Eisele, Holger; Greif, Ludwig A.Th; Hoffmann, Axel; Maultzsch, Janina; Müller, Marcus; Poliani, Emanuele; Schmidt, Gordon; Veit, Peter; Wagner, Markus R. (Springer Science and Business Media Deutschland GmbH, 2020)
Advanced characterization methods with nanoscale resolution are powerful tools in order to overcome the continuing challenges in the optimization of nitride semiconductor nanostructures for more efficient nanophotonic devices in the UV and green spectral range. This chapter is devoted to the study of optical, electronic, and structural properties of these nitride based nanostructures. In the first part, we discuss several state-of-the-art nanoscale characterization techniques including scanning transmission electron microscopy cathodoluminescence (STEM-CL), tip-enhanced Raman spectroscopy (TERS), micro-photoluminescence (µPL), X-ray diffraction (XRD), and scanning tunneling microscopy and spectroscopy (STM/STS). This selection of complementary microscopic and spectroscopic techniques provides unique insights into a multitude of nanostructure properties such as charge carrier excitation, relaxation, diffusion, and recombination dynamics, vibrational and structural properties including strain, segregation, as well as clustering, and surface and interface morphology. In the second part, we apply and combine these techniques to obtain detailed information on nanoscale properties of nitride based micro-columns, quantum wires, and heterostructures. The study of these nitride nanostructures provides not only insight into device limitations, but also contributes to the fundamental understanding of structural and optical properties of III-nitride nanostructures.
CRIS-Team Scopus Importer:2022-04-14